Desenvolvimento e aplicação de métodos analíticos verdes para a extração de flavonoides a partir de resíduos de Passiflora edulis sims f. Flavicarpa Deg. - Lopes, Ana Paula (Universidade Federal de São Carlos, 2018)
The concepts developed in this dissertation were guided by biorefinery assumptions, in which residues such as food peels can be enriched. In this sense, this research had as its main objective to develop, validate and apply green methods for the extraction of flavonoids from the peel of Passiflora edulis Sims (yellow passion fruit), which is here taken as study matrix due to its antioxidant activity, among other pharmacological effects. The three studied analytical methods comprised the extraction with solvent using ultra-turrax, ultrasound and microwave equipment, from which three flavonoids could be extracted: orientin, isoorientin and isovitexin, which were determined by UPLC-PDA. The green character of each method was analysed by means of the Green Star metric which, allied to analytical criteria, made it possible to find the best procedure for removing the flavonoids of interest in the samples. It is important to emphasize that UPLC and the application of chemometrics are associated to the choice of solvents and other ideally innocuous and renewable materials could also contribute to increase the green character of the whole study. At the end of this work, it was observed that, among the evaluated extraction methods, the most efficient and green-characterized experiment was based on ultra-turrax (exp.8), which made it possible to extract the selected flavonoids in greater quantity from the residues of sour passion fruit.
Development and deployment of green analytical methods for the extraction of flavonoids from Passiflora Edulis Sims f. Flavicarpa Deg. Residues
Keywords: Biorrefinaria; Maracujá; Métodos analíticos verdes de extração; Biorefinery; Passion fruit; Green analytical methods of extraction; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA